Positive electrode material, positive electrode plate and secondary battery
By using the concentration distribution of specific element M and appropriate amount of agglomerate particles in the positive electrode material of lithium-ion batteries, the problem of insufficient circulation stability and gas production performance of the positive electrode material is solved, and higher circulation stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411967110.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The circulation stability and gas production performance of existing lithium-ion battery positive electrode materials are insufficient and need to be improved.
A positive electrode material is used, which consists of particles including Na, K, Cs, Mg, Ca, Sr or Ba elements. The average concentration of the cut-section element M of the particles satisfies 1.2≤X2/X1≤20 between the central region and the surface region. Combined with an appropriate amount of agglomerated particles, the particle structure and distribution are controlled through spray pyrolysis method and sintering process.
By controlling the concentration distribution of element M and the proportion of agglomerates, appropriate compressive stress is formed, lattice volume changes during charging and discharging, the cyclic stability and rate performance of the positive electrode material are improved, and gas production is reduced.
Smart Images

Figure CN119725486A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, zero pollution, zero emissions and small size. As the main component of lithium-ion batteries, cathode materials play a decisive role in the capacity, performance and cost of batteries. However, the current cathode materials need to improve their cycle stability and gas production performance. Summary of the invention
[0003] In view of this, in order to solve at least one of the above defects, the present application provides a positive electrode material to improve the cycle stability and gas production performance of the positive electrode material.
[0004] In addition, the present application also provides a positive electrode sheet and a secondary battery using the positive electrode material.
[0005] The present application provides a positive electrode material, including an element M, where the element M is selected from at least one of Na, K, Cs, Mg, Ca, Sr or Ba. The positive electrode material includes a plurality of particles, and the cross-section of the particle includes a central region and a surface region. The cross-section of the particle is tested by an energy dispersive spectrometer (EDS), and the average concentration of the element M in the central region is measured to be X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20. The particles include primary particles and agglomerate particles. The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K. The total number of the primary particles and the agglomerate particles in the SEM image of the positive electrode material is N, and the number of agglomerates is n, and n and N satisfy: n / N<1%, wherein the agglomerate is formed by agglomerating 5 or more primary particles with a particle size of less than 1 μm.
[0006] In some embodiments, 3.3≤X2 / X1≤9.5.
[0007] In some embodiments, 0.5%≤n / N<1%.
[0008] In some embodiments, the maximum distance between any two points on the agglomerate particles is less than 4 μm.
[0009] In some embodiments, the concentration of the element M is 10 ppm to 400 ppm based on the mass of the positive electrode material.
[0010] In some embodiments, the positive electrode material is a single crystal material, and the average particle size of primary particles is 1 μm to 5 μm.
[0011] In some embodiments, the lattice strain ε of the positive electrode material is less than 0.1%.
[0012] In some embodiments, the general formula of the positive electrode material is: Li a Ni b Co c Mn d O2, wherein 0.95≤a≤1.2, 0<b≤1, 0<c≤1, 0<d≤1, b+c+d=1, and the element Q is selected from at least one of Mn and Al.
[0013] In some embodiments, the positive electrode material further contains element N, and element N is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y; based on the mass of the positive electrode material, the concentration of element N is less than 5000 ppm.
[0014] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g to 0.9m 2 / g.
[0015] In some embodiments, the tap density of the positive electrode material is: ρ1>2.0 g / cm 3 .
[0016] In some embodiments, the powder compaction density of the positive electrode material is ρ2: ρ2 ≥ 2.8 g / cm 3 .
[0017] In some embodiments, the particle size of the positive electrode material satisfies: 1.0≤(D90-D10) / D50≤1.5.
[0018] The present application also provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode material.
[0019] The present application also provides a secondary battery, including a shell, an electrode assembly, and an electrolyte or an electrolyte, the electrode assembly and the electrolyte or the electrolyte are both located in the shell, the electrode assembly includes a separator and a negative electrode plate, the electrode assembly also includes a positive electrode plate, and the separator is arranged between the positive electrode plate and the negative electrode plate.
[0020] In the present application, the concentration of the element M in the positive electrode material in the particles satisfies 1.2≤X2 / X1≤20, so that the content of the element M near the surface area of the particles is relatively high, and the M element increases the unit cell volume of the surface area of the particles, while the content of the element M near the central area of the particles is relatively small, so that the unit cell volume at the central area of the particles is relatively small, thereby forming a compressive stress from the surface to the center of the particles. The compressive stress can suppress the change of the lattice volume during the charge and discharge process, thereby improving the gas production performance of the positive electrode material and improving the long-term cycle performance of the positive electrode material. At the same time, combined with the range of the proportion of agglomerates in the present application, an appropriate amount of agglomerate particles can shorten the transmission channel for lithium ion deintercalation during the charge and discharge process, which is beneficial to the diffusion and transmission of lithium ions, thereby helping to reduce the internal stress caused by lithium ion deintercalation during the charge and discharge process. At the same time, the strength of the agglomerate particles is relatively high, which can reduce the particle rupture phenomenon during the pole piece rolling process, and the exposed surface of the fine powder and the particles is greatly reduced, thereby improving the gas production phenomenon, thereby synergistically improving the cycle stability and rate performance of the secondary battery.
[0021] Main component symbols
[0022] The electrode assembly 100 includes a positive electrode sheet 101 , a negative electrode sheet 102 and a separator 103 . BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0024] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0025] Figure 3 In the figure, (a) and (b) are respectively the content distribution diagrams of element K inside the single crystal particles in Example 1 and Comparative Example 2 of the present application.
[0026] Figure 4 In the figure, (a) and (b) are scanning electron microscope (SEM) images of high-power cross-sections of the positive electrode materials in Example 1 and Comparative Example 2 of the present application, respectively.
[0027] Figure 5 Schematic diagram of the structure of the concentration distribution of element M in this application. DETAILED DESCRIPTION
[0028] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0029] An embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0030] The outer shell can be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it can also be a steel shell battery, an aluminum shell battery, etc.
[0031] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103, wherein the separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. Figure 1 During discharge, active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode plate 102, pass through the electrolyte through the separator 103, reach the positive electrode plate 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), and generate electrons from the negative electrode plate 102 through the external circuit to the positive electrode plate 101. The reverse movement of the electrons forms an electric current that can be used by electrical appliances. When charging, please refer to Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode plate 101, pass through the isolation membrane 103 through the electrolyte, reach the negative electrode plate 102 and are inserted into the lattice of the negative electrode material.
[0032] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.
[0033] The present application also provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode material.
[0034] An embodiment of the present application provides a positive electrode material, including an element M, wherein the element M is selected from at least one of Na, K, Cs, Mg, Ca, Sr or Ba. The positive electrode material includes a plurality of particles, and a cross section of the particle includes a central region and a surface region. The cross section of the particle is tested by an energy dispersive spectrometer (EDS), and an average concentration of the element M in the central region is measured to be X1, and an average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; the particles of the positive electrode material include primary particles and agglomerate particles, and a SEM image of the positive electrode material is measured by a scanning electron microscope (SEM) at a magnification of 3K. In the SEM image of the positive electrode material, the total number of primary particles and agglomerate particles is N, the number of agglomerates is n, and n and N satisfy: n / N<1%.
[0035] In the present application, the concentration of element M in the particles is controlled to satisfy 1.2≤X2 / X1≤20, so that the content of element M near the surface area of the particles is relatively high, and the M element increases the unit cell volume of the surface area of the particles, while the content of element M near the central area of the particles is relatively small, so that the unit cell volume at the central area of the particles is relatively small, thereby forming a compressive stress from the surface to the center of the particles. The compressive stress can inhibit the change of the lattice volume during the charge and discharge process, inhibit the generation or diffusion of particle cracks, and thus improve the gas production performance of the positive electrode material and improve the long-term cycle performance of the positive electrode material. At the same time, combined with the range of the proportion of agglomerates in the present application, an appropriate amount of agglomerate particles can shorten the transmission channel for lithium ion deintercalation during the charge and discharge process, which is beneficial to the diffusion and transmission of lithium ions, thereby helping to reduce the internal stress caused by lithium ion deintercalation during the charge and discharge process. At the same time, the strength of the agglomerate particles is relatively high, which can reduce the particle rupture phenomenon during the pole piece rolling process, and the exposed surface of the fine powder and the particles is greatly reduced, thereby improving the gas production phenomenon, thereby synergistically improving the cycle stability and rate performance of the secondary battery.
[0036] It should be noted that the agglomerates are formed by the agglomeration of 5 or more particles with a particle size of less than 1 μm, and the maximum distance between any two points on the agglomerate particles is less than 4 μm. For the agglomerates, the strength of the agglomerate particles is relatively high, which can reduce the particle breakage phenomenon during the electrode rolling process, and the exposed surface of the fine powder and particles is greatly reduced, thereby improving the gas production phenomenon. Moreover, the particles of the positive electrode material have good dispersion, so that the compaction density of the positive electrode material can be maintained at a high level, thereby improving the capacity and long cycle performance of the positive electrode material.
[0037] When the ratio of n / N is large, such as greater than or equal to 1%, it means that the number of particle agglomerates increases. Although the compaction density of the positive electrode material can be improved, the compaction density of the positive electrode sheet decreases due to the low particle strength of the agglomerates. During the rolling process of the sheet, the agglomerates are easily broken, the exposed surface of the positive electrode material increases, and the side reactions with the electrolyte increase, affecting the capacity of the positive electrode material and the long-cycle stability.
[0038] When X2 / X1<1.2, the unit cell volume of the surface area of the particle is evenly distributed with the unit cell volume of the center area, and it is difficult to form compressive stress from the surface area to the center area. When X2 / X1>20, too much element M will be enriched on the surface of the particle, occupying the lattice lithium site, affecting the transmission and diffusion of lithium ions, and reducing the rate performance of the secondary battery.
[0039] In some embodiments, the ratio of X2 / X1 can be 1.2, 1.5, 2, 5, 7, 9, 10, 12, 14, 15, 16, 18, 19, 20, or any value within the range formed by any two of the above values. In some embodiments, n / N can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.95%, or any value within the range formed by any two of the above values.
[0040] In some embodiments, 3.3≤X2 / X1≤9.5. This is beneficial for the particles to form a suitable compressive stress from the surface toward the center, which can inhibit lattice expansion during charge and discharge, further improve the cycle stability and rate performance of the secondary battery, and reduce gas production.
[0041] In some embodiments, 0.5%≤n / N<1%. This is beneficial to improving the energy density of the secondary battery while maintaining a good capacity of the positive electrode material, and further improving the cycle stability and rate performance of the secondary battery and reducing gas production.
[0042] In some embodiments, based on the mass of the positive electrode material, the concentration of element M is 10ppm to 400ppm. The concentration of element M is within the above-mentioned suitable range, which is conducive to making the particles of the positive electrode material contain suitable element M, and making element M maintain a suitable unit cell volume size, which is conducive to suppressing the lattice strain generated by the positive electrode material during long cycles, further improving the cycle stability of the positive electrode material, and taking into account the positive electrode material having good rate performance and cycle performance. If the concentration of element M in the positive electrode material is large, the particles will contain more element M, resulting in a large change in the unit cell volume, reducing the structural stability of the positive electrode material, which is not conducive to improving the cycle stability of the positive electrode material. In some embodiments, the concentration of element M can be 10ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm or any value within the range composed of any two of the above values.
[0043] In some embodiments, the positive electrode material is a single crystal material, and the average particle size of the primary particles is 1 μm to 5 μm. The average particle size of the primary particles is within a suitable range, which can be compatible with the secondary battery having good rate performance and reducing the amount of gas produced. If the average particle size of the primary particles is large, such as greater than 5 μm, the average particle size of the primary particles is large, which affects the transmission of lithium ions and reduces the rate performance of the secondary battery; if the average particle size of the primary particles is small, such as less than 1 μm, the average particle size of the primary particles is small, and the contact area between the primary particles and the electrolyte in the positive electrode material is large, which will increase the gas production of the secondary battery. In some embodiments, the average particle size of the primary particles can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range composed of any two of the above values.
[0044] In the present application, the difference between a single crystal positive electrode material and a polycrystalline positive electrode material (i.e., a polycrystalline secondary particle) is that the smallest particle of a polycrystalline secondary particle is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For a single crystal positive electrode material, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for a single crystal positive electrode material, the morphology of the single crystal particles can be characterized by SEM, and it can be seen that the shape of the single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of the single crystal positive electrode material can also be characterized by EBSD. It can be observed by EBSD that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. Crystallographically, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more "single crystal morphology" positive electrode materials, which only show the large particle size of single crystals in size, which is different from the polycrystalline composed of many small primary particles. It can be understood that the single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also have a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particle" refers to the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particle is usually between 1μm and 5μm. In general, the particle roundness of the "quasi-secondary particle" is lower than the above-mentioned conventional "secondary particle".
[0045] In some embodiments, the lattice strain ε of the positive electrode material is less than 0.1%. By controlling the lattice strain of the positive electrode material within a suitable range, it is beneficial to reduce the diffusion energy barrier of lithium ions between microcrystals and increase the diffusion coefficient of lithium ions, thereby reducing the crystal volume change caused by lithium ion migration during the charge and discharge process of the secondary battery, inhibiting the generation of microcracks in the single crystal particles in the positive electrode material, thereby improving the cycle stability of the positive electrode material and reducing the direct current internal resistance (DCR) of the positive electrode material. In some embodiments, the lattice strain ε of the single crystal particles can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or any value within the range formed by any two of the above values.
[0046] In some embodiments, the general formula of the positive electrode material is: Li a Nib Co c Q d O2, where 0.95≤a≤1.2, 0<b≤1, 0<c≤1, 0<d≤1, b+c+d=1, and element Q is selected from at least one of Mn or Al. Element M is doped into the above-mentioned material. After element M enters the transition metal layer and occupies the site of the main element, element M will expand the transition metal layer spacing, thereby increasing the unit cell volume; when element M is enriched close to the particle surface, the unit cell volume of the surface area of the particle will be larger than the unit cell volume of the center area of the particle, and the stress in the surface area of the particle is larger, thereby generating compressive stress toward the center of the particle. It should be noted that for element M selected from at least one of Na, K, Cs, Mg, Ca, Sr or Ba, for example, when element M is Ca, due to Ca 2+ The ionic radius of Ni is 99 pm, while 2+ The ionic radius of Co is 72 pm. 2+ The ionic radius of Mn is 74 pm. 2+ The ionic radius is 80 pm. 2+ When atoms enter the transition metal layer of the positive electrode material to replace Ni / Co / Mn elements, Ca with large ion radius 2+ The interlayer spacing of the transition metal will be enlarged, thereby increasing the unit cell volume; and when the doping element Ca 2+ When the distribution is enriched near the surface, the average unit cell volume of the particles decreases from the surface to the center, and compressive stress is generated in the particles. This compressive stress can inhibit the expansion at the center of the particles, and can inhibit the internal stress and fatigue cracks generated inside the particles due to the uneven distribution of lattice expansion of the particles during the lithium ion insertion and extraction process of the single crystal material during the charge and discharge process of the positive electrode material due to the long lithium ion transmission distance, thereby inhibiting the initiation and propagation of cracks in the particles, thereby improving the long-term electrochemical performance of the secondary battery.
[0047] In some embodiments, the positive electrode material further contains element N, and element N is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y; based on the mass of the positive electrode material, the concentration of element N is less than 5000ppm. In the above-mentioned positive electrode material, the doping of an appropriate amount of element N can stabilize the positive electrode material and further improve the specific capacity and cycle stability of the positive electrode material. Based on the mass of the positive electrode material, the concentration of element N is less than 5000ppm. The content of doped element N is within a suitable range, which is conducive to further improving the specific capacity and cycle stability of the positive electrode material. If the concentration of element N is large, such as greater than 5000ppm, too much element N will be enriched on the surface of the particles, which is easy to cause agglomeration and adhesion of the particles. In the process of preparing the positive electrode sheet from the positive electrode material, compacting the positive electrode sheet is easy to cause the cracking of the agglomerated particles, which will increase the side reaction of the electrolyte and the positive electrode material in the secondary battery, and affect the long-term electrochemical performance of the secondary battery. In some embodiments, the concentration of element N can be 10ppm, 100ppm, 200ppm, 500ppm, 600ppm, 800ppm, 1000ppm, 1500ppm, 1700ppm, 1900ppm, 2000ppm, 2500ppm, 2700ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or any value in the range formed by any two of the above values. In some embodiments, the concentration of element N is 1000ppm to 3000ppm.
[0048] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g to 0.9m 2 / g. The specific surface area of the positive electrode material is within the above range, which is conducive to reducing the contact between the positive electrode material and the electrolyte, reducing the occurrence of side reactions, and making the positive electrode material have a good discharge capacity. In some embodiments, the specific surface area of the positive electrode material can be 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g or any value within the range formed by any two of the above values.
[0049] In some embodiments, the tap density of the positive electrode material is: ρ1>2.0 g / cm 3 The tap density of the positive electrode material is within a suitable range, which is conducive to improving the compaction of the electrode sheet containing the positive electrode material and improving the energy density of the secondary battery. In some embodiments, the tap density of the positive electrode material can be 2.5 g / cm 3 、3.0g / cm 3、3.5g / cm 3 , 4.0g / cm 3 , 4.5g / cm 3 , 5.0g / cm 3 Or any value within the range formed by any two of the above values.
[0050] In some embodiments, the powder compaction density of the positive electrode material is ρ2: ρ2 ≥ 2.8 g / cm 3 The compaction density of the positive electrode material powder is within a suitable range, which is conducive to further improving the compaction degree of the electrode sheet containing the positive electrode material and improving the energy density of the secondary battery. In some embodiments, the compaction density of the positive electrode material powder can be 2.8 g / cm 3 、3.0g / cm 3 、3.2g / cm 3 、3.8g / cm 3 , 4g / cm 3 , 4.5g / cm 3 Or any value within the range formed by any two of the above values.
[0051] In some embodiments, the particle size of the positive electrode material satisfies: 1.0≤(D90-D10) / D50≤1.5. The particle size distribution of the positive electrode material satisfies the above relationship, which is conducive to further improving the compaction of the electrode sheet containing the positive electrode material and improving the energy density of the secondary battery. The particle size D50 of the positive electrode material represents the particle size of the positive electrode material particles in the volume-based particle size distribution measured from the small particle size to reach 50% of the cumulative volume, that is, the volume of the positive electrode material particles smaller than this particle size accounts for 50% of the total volume of the positive electrode material particles. The particle size D90 of the positive electrode material represents the particle size of the positive electrode material particles in the volume-based particle size distribution measured from the small particle size to reach 90% of the cumulative volume. The particle size D10 of the positive electrode material represents the particle size of the positive electrode material particles in the volume-based particle size distribution measured from the small particle size to reach 10% of the cumulative volume. (D90-D10) / D50 is expressed as a "Span value".
[0052] The present application also provides a method for preparing a positive electrode material, comprising the following steps:
[0053] S1: A mixed salt solution containing Ni salt, Co salt and Q salt is prepared according to a set ratio of Ni:Co:Q, and a certain amount of salt solution containing element M is added to the mixed salt, mixed evenly, to obtain a mixed solution; and the mixed solution is prepared into an oxide precursor by a spray pyrolysis method. Element Q is selected from at least one of Mn and Al.
[0054] In this step, Ni salt, Co salt and Q salt are all from the recovered positive electrode material. Specifically, the recovered ternary positive electrode material is subjected to component detection to confirm the proportion of the main element content in the recycled material and the type and proportion of the M element present, and then the positive electrode material with the confirmed composition and the pure metal of Ni / Co / Q are prepared into a mixed salt solution according to the final target Ni:Co:Q ratio. Element Q is selected from at least one of Mn or Al. It can be understood that in some other embodiments, Ni salt, Co salt and Q salt can also come from commercially available products. Ni salt, Co salt and Q salt can be any one of sulfate, nitrate, chloride, carbonate or phosphate.
[0055] If the recovered ternary cathode material contains a doping element M, the concentration of the doping element M can be adjusted by adding a target doping element concentration so that the concentration of the doping element M is the target concentration, that is, a mixed solution is obtained. The salt of element M includes at least one of chloride, sulfate, sulfite, nitrate, carbonate or phosphate of element M.
[0056] Optionally, in the configuration process of the mixed solution, the total metal concentration in the mixed solution is in the range of 2mol / L-8mol / L, and the mass percentage concentration of element M in the precursor solution is 0.01% to 0.06%. Specifically, the mass percentage concentration of element M in the precursor solution can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05% or 0.06%, etc., and of course it can also be other values within the above range, which are not limited here. By controlling the mass percentage concentration of element M in the precursor solution within the range, the content of element M in the prepared positive electrode material can be made to meet the range of 10ppm to 400ppm. And within this range, it is conducive to the moderate solid content of the spray droplets formed in the subsequent spraying step, and the solid phase as a nucleation site is conducive to the rapid solidification and nucleation of the droplets.
[0057] In this step, the spray pyrolysis method includes a spraying step and an annealing step. In the spraying process of the spraying step, the atomizing air flow rate of the spray is controlled to be 100-300m 3 and atomization pressure of 400-700Kpa; in this process, large atomization flow and atomization pressure can make it possible to separate ions with different ion radii in the droplets during the spraying process, and the M metal element will be distributed on the droplet surface.
[0058] In the annealing step, the liquid treated in the spraying step is annealed at a temperature of 800°C-1200°C. The higher annealing temperature is to enable the droplets to rapidly pyrolyze and nucleate, and to retain the M metal element distributed on the particle surface to a greater extent. In this process, by controlling different atomization air flow rates, atomization pressures and annealing temperatures, the internal and external distribution difference of the M element can be adjusted so that the value range of the M element is 1.2≤X2 / X1≤20.
[0059] S2: crushing the prepared oxide precursor to a particle size D50 of 2.0 μm-4.0 μm, uniformly mixing the crushed oxide precursor with a lithium salt and a metal compound containing the N element to obtain a mixture, and sintering the mixture once to obtain a sintered product.
[0060] The particle size D50 of the crushed oxide precursor is within the above range, which is conducive to the subsequent preparation of less positive electrode material powder and a more rounded surface of the single crystal particles.
[0061] The metal oxide containing element N is selected from any one or more of ZrO2, TiO2, Al2O3, CoO, MgO, WO3, CeO2, and Y2O3; preferably, the metal oxide containing element N is CeO2 and / or WO3, and further preferably, the metal oxide containing element N is CeO2.
[0062] As an embodiment of the present invention, in step 2, the oxide precursor, the lithium source, and the metal oxide containing the element N are mixed in a mass ratio of 1: (0.4-0.8): (0.003-0.006). Specifically, the oxide precursor, the lithium source, and the metal oxide containing the element N are mixed in a mass ratio of 1: 0.4: 0.003, 1: 0.5: 0.004, 1: 0.6: 0.006, 1: 0.5: 0.003, 1: 0.5: 0.005, 1: 0.8: 0.003, 1: 0.8: 0.006, 1: 0.4: 0.006 or 1: 0.5: 0.004. Of course, it can also be other values within the above range, which are not limited here. By limiting the mass ratio of several reaction materials of the oxide precursor, the lithium source, and the metal oxide containing the element N, a positive electrode material having the chemical formula described in this application can be obtained.
[0063] The lithium salt may be at least one of lithium carbonate, lithium hydroxide and lithium nitrate.
[0064] In step S2, during the first sintering, the heating rate in the heating stage is controlled at 3°C / min or less, and the slow heating can make the single crystal nucleation more complete.
[0065] In step S2, during sintering, the holding time is more than 8 hours, the single crystal particles grow more fully, and fewer single crystal agglomerates are obtained. Optionally, in step S2, the sintering method can be selected as pulse sintering, which can reduce the cation mixing caused by long-term high temperature. At the same time, because the high temperature time is short, the single crystal particles will not grow excessively, the sintered single crystal particles are close in size, and there is less fine powder. The specific steps are as follows: (1) In an oxygen or air atmosphere, place the mixture in a furnace with a furnace pressure of 2Pa to 30Pa, and sinter at a temperature T2 of 800℃ to 1000℃ for 1 to 2 hours. (2) Then sinter at a temperature T3 (T3 = T2-30℃) for 1h to 2h. Repeat the temperatures of T2 and T3 so that the total sintering time of the mixture at T2 temperature is 4h to 8h, and the total sintering time of the mixture at T3 temperature is 4h to 8h. (3) Finally, the temperature is kept at T4 (T4 = T3-10°C) for 4 hours to anneal the sintered material, repair the microcrystalline boundaries, and achieve uniform particle growth, thereby obtaining a matrix material. Through the above steps, the value range of agglomerates can be controlled to be less than 1%.
[0066] Optionally, the sintered product is subjected to air flow pulverization, and the pulverized particle size D50 is controlled within 3.0 μm-5.0 μm. This particle size range corresponds to the D50 particle size range of the precursor, and the single crystal particles can be pulverized.
[0067] S3: The crushed sintered product is uniformly mixed with the coating agent, and after uniform mixing, secondary sintering is performed in an oxygen atmosphere, and the sintered sample is screened and demagnetized to obtain a finished product, wherein the coating agent contains element N.
[0068] In step S3, coating the sintered product with a coating agent can improve the electrochemical properties of the single crystal material.
[0069] As an embodiment of the present invention, the coating agent used in the coating treatment is selected from at least one of ZrO2, TiO2, Al2O3, CoO, MgO, WO3, CeO2, and Y2O3. The content of element N in the positive electrode material is 0ppm to 5000ppm. Specifically, the content of element N in the positive electrode material can be 0ppm, 5ppm, 100ppm, 500ppm, 1000ppm, 1500ppm, 1800ppm, 2000ppm, 2400ppm, 2800ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 4800ppm or 5000ppm, etc., and of course it can also be other values within the above range, which is not limited here. When the concentration of element N is within the above range, the crystal structure of the positive electrode material can be stabilized, the ionic conductivity can be improved, and the side reactions between the positive electrode material and the electrolyte can be delayed.
[0070] In step S3, the secondary sintering temperature is 500°C-800°C, and the sintering time is 6h-10h.
[0071] Negative electrode
[0072] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0073] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.
[0074] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.
[0075] The negative electrode active material includes a material that reversibly intercalates / deintercalates lithium ions. In some embodiments, the material that reversibly intercalates / deintercalates lithium ions includes a carbon material. In some embodiments, the carbon material can be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable batteries. In some embodiments, the carbon material includes, but is not limited to: crystalline carbon, amorphous carbon, or a mixture thereof. Crystalline carbon can be amorphous, flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0076] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material includes, but is not limited to: lithium metal, structured lithium metal, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or any combination thereof. The silicon-carbon composite refers to a composite containing at least about 5 wt% silicon based on the weight of the silicon-carbon negative electrode active material.
[0077] In some embodiments, the negative electrode active material comprises at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon alloy, or silicon oxide.
[0078] When the negative electrode includes a silicon-carbon compound, based on the total weight of the negative electrode active material, silicon:carbon=about 1:10-10:1, and the median particle size Dv of the silicon-carbon compound is 50The negative electrode active material layer may be formed by a method such as evaporation, sputtering, or plating. When the negative electrode includes lithium metal, the negative electrode active material layer may be formed by, for example, a spherical and twisted conductive skeleton and metal particles dispersed in the conductive skeleton. In some embodiments, the spherical and twisted conductive skeleton may have a porosity of about 5% to about 85%. In some embodiments, a protective layer may also be provided on the lithium metal negative electrode active material layer.
[0079] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0080] In some embodiments, the conductive material includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0081] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof.
[0082] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include water, etc., but is not limited thereto.
[0083] Isolation film
[0084] The material and shape of the separator used in the secondary battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0085] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.
[0086] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.
[0087] The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0088] Electrolyte
[0089] According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.
[0090] The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application can be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or ethyl propionate (EP).
[0091] In some embodiments, the organic solvent includes an ether solvent, for example, at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2 (LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2 (LiBOB) or lithium di(oxalate borate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.
[0092] According to some embodiments of the present application, the secondary battery of the present application includes, but is not limited to: a lithium ion battery. In some embodiments, the secondary battery includes a lithium ion battery.
[0093] The present application also applies secondary batteries to electronic devices to power loads in the electronic devices. The electronic devices of the present application are not particularly limited. In some embodiments, the electronic devices of the present application include, but are not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0094] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0095] Example 1
[0096] (1) Metal salts of Ni, Co, and Mn are prepared into a chloride solution in a molar ratio of Ni:Co:Mn=55:15:30, and a chloride solution of K is added to the chloride solution to prepare a precursor solution. The mass ratio content of K element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and K in the precursor solution is 5 mol / L.
[0097] (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 200m 3 / h, the atomization pressure is 550Kpa, the pyrolysis temperature is 500℃, and the annealing temperature is 1000℃.
[0098] (3) The oxide precursor is crushed, and the median particle size D50 of the volume distribution of the crushed oxide precursor is 3.24 μm; 400 g of the crushed oxide precursor, 186.72 g of lithium carbonate and 1.8 g of Y2O3 are uniformly mixed to obtain a mixture, and pulse sintering is performed; the mixture is sintered in an oxygen or air atmosphere at a furnace pressure of 20 Pa and a temperature T2 of 950°C for 1 to 2 h, and a temperature T3: T2-30°C for 2 h; the temperatures of T2 and T3 are repeated, so that a total of 8 h is sintered at the temperature T2 and a total of 8 h is sintered at the temperature T3; finally, the mixture is kept warm at T4: T3-10°C for 4 h to anneal the material, and finally a primary sintered product is obtained.
[0099] (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0100] Example 2
[0101] This embodiment provides a positive electrode material, and the preparation process is as follows:
[0102] (1) Metal salts of Ni, Co, and Mn are prepared into a nitrate solution in a molar ratio of Ni:Co:Mn=60:10:30, and a Mg sulfate solution is added to the nitrate solution to prepare a precursor solution. The mass ratio content of Mg element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and Mg in the precursor solution is 5 mol / L.
[0103] (2) Spray pyrolysis includes spraying the precursor solution and then annealing it to produce an oxide precursor, wherein the atomizing air flow rate of the spraying process is 220m 3 / h, the atomization pressure is 500Kpa, the pyrolysis temperature is 600℃, and the annealing temperature is 900℃.
[0104] (3) The oxide precursor is crushed, and the median particle size D50 of the volume distribution of the crushed oxide precursor is 3.16 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of Y2O3 to obtain a mixture, and pulse sintering is performed; the mixture is sintered in an oxygen or air atmosphere at a furnace pressure of 20 Pa and a temperature T2 of 940°C for 1 to 2 h, and a temperature T3: T2-30°C for 2 h; the temperatures of T2 and T3 are repeated, so that a total of 8 h is sintered at the temperature T2 and a total of 8 h is sintered at the temperature T3; finally, the mixture is kept warm at T4: T3-10°C for 4 h to anneal the material, and finally a primary sintered product is obtained.
[0105] (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.1 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0106] Example 3
[0107] The difference between Example 3 and Example 1 is that in step (1), "K chloride solution" is replaced by "Ca chloride solution". In step (2), the atomizing air flow rate of the spray treatment is 180m 3 / h, the atomization pressure is 600Kpa, the pyrolysis temperature is 800°C, and the annealing temperature is 1100°C. In step (3), the volume distribution median particle size D50 of the pulverized oxide precursor is 3.36μm. In step (4), the volume distribution median particle size D50 of the pulverized material is 4.8μm. The remaining steps are the same as in Example 1.
[0108] Example 4
[0109] The difference between Example 4 and Example 1 is that in step (1), "K chloride salt solution" is replaced by "Ba chloride salt solution". In step (2), the atomization pressure of the spray treatment is 500Kpa and the pyrolysis temperature is 800°C. In step (3), the volume distribution particle size median D50 of the crushed oxide precursor is 3.05μm. In step (4), the volume distribution particle size median D50 of the crushed material is 3.5μm. The remaining steps are the same as in Example 1.
[0110] Example 5
[0111] The difference between Example 5 and Example 1 is that in step (1), "K chloride solution" is replaced by "Sr nitrate solution". In step (2), the atomizing air flow rate of the spray treatment is 150m 3 / h, the atomization pressure is 650Kpa, the pyrolysis temperature is 700°C, and the annealing temperature is 800°C. In step (3), the volume distribution median particle size D50 of the pulverized oxide precursor is 3.5μm. In step (4), the volume distribution median particle size D50 of the pulverized material is 4.2μm. The remaining steps are the same as in Example 1.
[0112] Example 6
[0113] The difference between Example 6 and Example 1 is that in step (1), "K chloride solution" is replaced by "K chloride solution and Mg chloride solution", and the mass ratio of K element and Mg element in the precursor solution is 0.02%. In step (2), the pyrolysis temperature of the spray treatment is 900°C. In step (3), the volume distribution particle size median D50 of the crushed oxide precursor is 3.28μm. In step (4), the volume distribution particle size median D50 of the crushed material is 4.0μm. The remaining steps are the same as in Example 1.
[0114] Example 7
[0115] Example 7 The difference between Example 1 and Example 1 is that in step (1), "K chloride solution" is replaced by "K sulfate solution and Ca sulfate solution", and the mass ratio content of K element and Ca element in the precursor solution is 0.02%. In step (2), the atomizing air flow rate of the spray treatment is 240m 3 / h, the atomization pressure is 450Kpa, the pyrolysis temperature is 600°C, and the annealing temperature is 950°C. In step (3), the volume distribution median particle size D50 of the pulverized oxide precursor is 2.96μm. In step (4), the volume distribution median particle size D50 of the pulverized material is 4.7μm. The remaining steps are the same as in Example 1.
[0116] Example 8
[0117] Example 8 The difference from Example 1 is that in step (1), "K chloride solution" is replaced by "K chloride solution and Ba chloride solution", and the mass ratio of K element and Ba element in the precursor solution is 0.02%. In step (2), the atomization pressure of the spray treatment is 600Kpa, and the pyrolysis temperature is 700°C. In step (3), the median D50 of the volume distribution particle size of the crushed oxide precursor is 3.1μm. In step (4), the median D50 of the volume distribution particle size of the crushed material is 3.7μm. The remaining steps are the same as Example 1.
[0118] Example 9
[0119] Example 9 The difference of Example 1 is that in step (1), "K chloride solution" is replaced by "K chloride solution and Sr chloride solution", and the mass ratio content of K element and Sr element in the precursor solution is 0.02%. In step (2), the atomizing air flow rate of the spray treatment is 180m 3 / h, the atomization pressure is 500Kpa, and the pyrolysis temperature is 650°C. In step (3), the volume distribution particle size median D50 of the crushed oxide precursor is 3.25μm. In step (4), the volume distribution particle size median D50 of the crushed material is 4.3μm. The remaining steps are the same as in Example 1.
[0120] Example 10
[0121] Example 10 The difference from Example 1 is that in step (1), "K chloride solution" is replaced by "Mg chloride solution and Ca chloride solution", and the mass ratio of Mg element and Ca element in the precursor solution is 0.03%. In step (2), the atomization pressure of the spray treatment is 580Kpa, and the pyrolysis temperature is 700°C. In step (3), the median D50 of the volume distribution particle size of the crushed oxide precursor is 3.75μm. In step (4), the median D50 of the volume distribution particle size of the crushed material is 4.8μm. The remaining steps are the same as in Example 1.
[0122] Embodiment 11
[0123] Example 11 The difference of Example 1 is that in step (1), "K chloride solution" is replaced by "Mg nitrate solution and Ba nitrate solution", and the mass ratio content of Mg element and Ba element in the precursor solution is 0.03%. In step (2), the atomizing air flow rate of the spray treatment is 150m 3 / h, the atomization pressure is 550Kpa, and the pyrolysis temperature is 800°C. In step (3), the volume distribution particle size median D50 of the pulverized oxide precursor is 3.21μm. In step (4), the volume distribution particle size median D50 of the pulverized material is 4.1μm. The remaining steps are the same as in Example 1.
[0124] Example 12
[0125] Example 12 The difference from Example 1 is that in step (1), "K chloride solution" is replaced by "Mg chloride solution and Sr chloride solution", and the mass ratio content of Mg element and Sr element in the precursor solution is 0.03%. In step (2), the atomizing air flow rate of the spray treatment is 120m 3 / h, the atomization pressure is 700Kpa, and the pyrolysis temperature is 900°C. In step (3), the volume distribution particle size median D50 of the pulverized oxide precursor is 3.19μm. In step (4), the volume distribution particle size median D50 of the pulverized material is 4.2μm. The remaining steps are the same as in Example 1.
[0126] Example 13
[0127] Example 13 The difference from Example 1 is that in step (1), "K chloride solution" is replaced by "Ca chloride solution and Ba chloride solution", and the mass ratio of Ca element and Ba element in the precursor solution is 0.03%. In step (2), the atomization pressure of the spray treatment is 600Kpa, and the pyrolysis temperature is 600°C. In step (3), the median particle size D50 of the volume distribution of the crushed oxide precursor is 3.38μm. In step (4), the median particle size D50 of the volume distribution of the crushed material is 4.2μm. The remaining steps are the same as Example 1.
[0128] Embodiment 14
[0129] Example 14 The difference from Example 1 is that in step (1), "K chloride solution" is replaced by "Ca nitrate solution and Sr nitrate solution", and the mass ratio of Ca element and Sr element in the precursor solution is 0.03%. In step (2), the atomization pressure of the spray treatment is 600Kpa, and the pyrolysis temperature is 1000°C. In step (3), the median D50 of the volume distribution particle size of the crushed oxide precursor is 3.48μm. In step (4), the median D50 of the volume distribution particle size of the crushed material is 4.4μm. The remaining steps are the same as Example 1.
[0130] Embodiment 15
[0131] Example 15 The difference from Example 1 is that in step (1), "K chloride salt solution" is replaced by "Ba chloride salt solution and Sr chloride salt solution", and the mass ratio of Ba element and Sr element in the precursor solution is 0.03%. In step (2), the pyrolysis temperature of the spray treatment is 600°C, and the temperature of the annealing treatment is 1200°C. In step (3), the median D50 of the volume distribution particle size of the crushed oxide precursor is 3.52μm. In step (4), the median D50 of the volume distribution particle size of the crushed material is 4.7μm. The remaining steps are the same as Example 1.
[0132] Example 16
[0133] Example 16 The difference from Example 1 is that in step (1), metal salts of Ni, Co, and Al are prepared into a nitrate solution in a molar ratio of Ni:Co:Al=50:20:30. In step (3), the volume distribution median particle size D50 of the crushed oxide precursor is 3.19 μm. In step (4), the volume distribution median particle size D50 of the crushed material is 4.4 μm. The remaining steps are the same as in Example 1.
[0134] Embodiment 17
[0135] Example 17 is different from Example 1 in that step (4) is not performed. The remaining steps are the same as Example 1.
[0136] Embodiment 18
[0137] The difference between Example 18 and Example 1 is that in step (1), the metal salts of Ni, Co and Mn are prepared into a nitrate solution according to the molar ratio of Ni:Co:Mn=70:10:20, and the mass ratio content of K element in the precursor solution is 0.04%; in step (2), the atomizing air flow rate of the spray treatment is 100m 3 / h, atomization pressure of 700Kpa, pyrolysis temperature of 400°C, and annealing temperature of 1200°C. In step (3), pulse sintering is selected for sintering; the mixed material is sintered for 1 to 2 hours in an oxygen or air atmosphere with a furnace pressure of 20Pa and a temperature T2 of 935°C. The other steps are the same as those in Example 1.
[0138] Embodiment 19
[0139] The difference between Example 19 and Example 1 is that in step (1), the metal salts of Ni, Co and Mn are prepared into a nitrate solution in a molar ratio of Ni:Co:Mn=80:10:10; in step (2), the atomizing air flow rate of the spray treatment is 300m 3 / h, the atomization pressure is 400Kpa, the pyrolysis temperature is 1000°C, and the annealing temperature is 500°C. In step (3), pulse sintering is selected for sintering; the mixed material is sintered in an oxygen or air atmosphere at a furnace pressure of 20Pa and a temperature T2 of 930°C for 1 to 2h, and the other steps are the same as those in Example 1.
[0140] Embodiment 20
[0141] The difference between Example 20 and Example 1 is that in step (1), the metal salts of Ni, Co and Mn are prepared into a nitrate solution according to the molar ratio of Ni:Co:Mn=90:5:5. In step (3), pulse sintering is selected for sintering; the mixture is sintered in an oxygen or air atmosphere at a furnace pressure of 20 Pa and a temperature T2 of 925°C for 1 to 2 hours, and the other steps are the same as in Example 1.
[0142] Comparative Example 1
[0143] The difference between Comparative Example 1 and Example 1 is that in step (1) and step (2), a hydroxide precursor with a molar ratio of Ni:Co:Mn=55:15:30 is synthesized by coprecipitation. In step (3), "Y2O3" is replaced by "CeO2". The remaining steps are the same as in Example 1.
[0144] Comparative Example 2
[0145] The difference between Comparative Example 2 and Example 1 is that in step (1) and step (2), a hydroxide precursor with a molar ratio of Ni:Co:Mn=55:15:30 is synthesized by coprecipitation. In step (3), "Y2O3" is replaced by "1.8gCeO2, 0.1g MgO, 0.1g KOH", and sintered at 960°C for 8h in a compressed air atmosphere to obtain a sintered product. The remaining steps are the same as those in Example 1.
[0146] Comparative Example 3
[0147] This comparative example provides a positive electrode material, and the positive electrode material provided in this comparative example is obtained by the following preparation method:
[0148] (1) Pure metal salts of Ni, Co, and Mn are prepared into a mixed nitrate solution in a molar ratio of Ni:Co:Mn=55:15:30, and the nitrate solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 220m 3 / h, the atomization pressure is 500Kpa, the pyrolysis temperature is 600℃, and the annealing temperature is 900℃.
[0149] (2) The oxide precursor is crushed and the crushing D50 is controlled to be 3.48 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and the mixture is sintered at 960° C. for 8 h in a compressed air atmosphere to obtain a sintered product.
[0150] (3) The obtained sintered material is crushed to a particle size D50 of 4.1 μm to obtain a crushed material; 300 g of the crushed material is mixed with 0.5 g of WO3, and sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material, and the sintered material is sieved and demagnetized to obtain a positive electrode material.
[0151] Comparative Example 4
[0152] (1) taking metal salts of Ni, Co, and Mn, preparing a nitrate solution in a molar ratio of Ni:Co:Mn=55:15:30, adding a K chloride solution to the nitrate solution to prepare a precursor solution, wherein the mass ratio content of K element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and K in the precursor solution is 5 mol / L;
[0153] (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 80m 3 / h, atomization pressure is 900Kpa, pyrolysis temperature is 1000℃, annealing temperature is 700℃;
[0154] (3) The oxide precursor is crushed, and the median particle size D50 of the volume distribution of the crushed oxide precursor is 3.24 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2 to obtain a mixture, and pulse sintering is performed; the mixture is sintered in an oxygen or air atmosphere at a furnace pressure of 20 Pa and a temperature T2 of 940°C for 1 to 2 h, and a temperature T3: T2-30°C for 2 h; the temperatures of T2 and T3 are repeated, so that a total of 8 h is sintered at the temperature T2 and a total of 8 h is sintered at the temperature T3; finally, the mixture is kept warm at T4: T3-10°C for 4 h to anneal the material, and finally a primary sintered product is obtained.
[0155] (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0156] Comparative Example 5
[0157] The difference between Comparative Example 5 and Example 19 is that in step (3), pulse sintering is not adopted, but two-stage sintering is adopted. The sintering temperature of the first stage is 830°C and the sintering time is 4 hours. The sintering temperature of the second stage is 930°C and the time is 4 hours.
[0158] The specific performance parameters of the positive electrode materials in the above embodiments and comparative examples are detailed in Tables 1 to 4.
[0159] The performance of the positive electrode materials prepared in the examples and comparative examples was tested using the following test methods and battery performance test methods.
[0160] Test method:
[0161] 1. The test method for the element concentration of M element, N element and main element is as follows:
[0162] Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool it and make the volume into 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times and test the content of the main elements Li / Ni / Co / Mn. Similarly, use Agilent 5110ICP-OES detection equipment to test the content of other elements such as M and N, and the content of M and N elements can be obtained.
[0163] 2. The test method for M element concentration distribution is as follows:
[0164] The test method for the average concentration X1 of the element M in the center area and the average concentration X2 in the surface area of the positive electrode material particles is as follows: use a Hitachi ion cutting instrument to prepare a cross-section sample, use a Hitachi S4800 scanning electron microscope to select a suitable cross-section field of view, and then use EDS to perform line scanning or point scanning on the particle cross section within the 5k field of view. For example, the point scanning method can be used to measure the content of the element M at 10 positions (generally at least 5 points) in the center area of the particle cross section, and the content of the element M is summed and averaged to obtain X1; measure the content of the element M at 10 positions in the surface area of the particle cross section, and the content of the element M is summed and averaged to obtain X2. Figure 5 As shown in the particle cross-sectional view, the radius of the particle is L, the area from the center of the particle to the distance L / 2 from the center of the particle is the central area, and the area from the position L / 2 of the particle to the surface of the particle is the surface area. When the positive electrode material contains two or more elements M, X1 and X2 of each element M are measured separately, and the X2 / X1 value of the corresponding element is calculated accordingly.
[0165] For point scanning and line scanning, combined Figure 5 The instructions are as follows:
[0166] Scan: In the center area ( Figure 5 5-10 points are selected for EDS measurement (inside the dotted circle shown in the figure), and the average value is taken to obtain the X1 value; in the surface area ( Figure 5 Select 5-10 points (outside the dotted circle shown) for EDS measurement and take the average value after measurement to get the X2 value.
[0167] Line scan: In the central area (i.e. Figure 5At least three line positions are randomly selected for line scanning (inside the dotted circle shown in the figure), and the average value is taken after measurement to obtain the X1 value; the surface area (i.e. Figure 5 At least three line positions are randomly selected for line scanning (outside the dotted circle shown in the figure), and the average value is taken after measurement to obtain the X2 value. In actual testing, point scanning and line scanning can also be used in combination.
[0168] 3. The calculation method of aggregate ratio n / N is as follows:
[0169] Hitachi S4800 scanning electron microscope was used to take 5 3K views of the sample at different positions. The sample was also cut and then 5 3K views of the sample at different positions were taken. The total number of particles N in the view was counted, and then the particle size in the view was measured using NanoMeasure software. After the measurement, the number of particle agglomerates n with a particle size of 5 or more particles below 1 micron was counted, and the maximum distance between any two points of the agglomerates was less than 4μm. Finally, the proportion of agglomerates n / N was calculated. It should be noted that the total number of particles N mentioned above includes primary particles and agglomerate particles.
[0170] 4. The test method for the specific surface area S1 of the positive electrode material is as follows:
[0171] The specific surface area was tested using an American Micrometer tester: the test was performed after degassing at 300°C in vacuum for 1 hour.
[0172] 5. The test method for the tap density ρ1 of the positive electrode material is as follows:
[0173] Dandong Better BT-303 was used to test the compacted density: vibration rate 3000 times / min, vibration time 1min, vibration amplitude 3mm±0.1mm.
[0174] 6. The test method for the compacted density ρ2 of the positive electrode material powder is as follows:
[0175] The compaction density of the powder was tested using a compaction density meter: 6t pressure for 30s.
[0176] 7. The particle size test method of the positive electrode material is as follows:
[0177] Malvern laser particle size tester MS 3000 was used to test the particle size of the positive electrode material.
[0178] 8. The scanning electron microscope test method of the positive electrode material is as follows:
[0179] Hitachi S4800 scanning electron microscope was used to observe the surface morphology and particle size of the samples.
[0180] 9. The test method for the average particle size of primary particles is as follows:
[0181] Hitachi S4800 scanning electron microscope was used to take 5 pictures of samples at different positions. The sample could also be cut into sections and 5 3K section views of the sample at different positions were taken at 3K. Nano Measure software was then used to measure the primary particle size in each view. After the measurement, the average primary particle size of the 5 views was taken to obtain the average primary particle size of the sample.
[0182] 10. The unit cell volume and lattice strain test methods are as follows:
[0183] The test was carried out using a Rigaku XRD diffractometer in the range of 10°-70° at a parameter of 1° / min and a step size of 0.005°. The tested XRD spectra were then Rietveld refined by GASA to obtain information such as unit cell volume, unit cell parameters (a, c) and peak shape parameters. The lattice strain was calculated based on the obtained peak shape parameters according to the Scherrer formula.
[0184] 11. The ternary cathode material products obtained in the above embodiments and comparative examples were assembled into button-type batteries using the following method and subjected to performance testing.
[0185] After the positive electrode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, NMP (N-methylpyrrolidone) is added to make a uniform slurry, the slurry is evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it is rolled at a pressure of 10Mpa and cut into a circular pole piece with a diameter of 14mm. The negative electrode uses a Li metal sheet with a diameter of 14mm. The lithium-ion battery is assembled according to the CR2025 button battery in industry. The diaphragm is a Cellgard diaphragm, and the electrolyte uses an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte are assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5ppm.
[0186] The button cell was tested for electrochemical cycle performance, capacity, rate performance, and first efficiency (first efficiency). The voltage range of the charge and discharge cycle was 2.8V-4.35V, the current size was 0.1C (20mAh / g), and the cycle test was performed at 0.5C charge and 1C discharge for 50 weeks. The capacity unit is mAh / g, and the first efficiency unit is %.
[0187] Capacity test method: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 2.8~4.35V, temperature condition is 25℃), charging at 0.1C, then discharging at 0.1C, constant voltage cut-off current is 0.005C, and the discharge capacity mAh / g is calculated.
[0188] Cycle test method: At 25°C, under the condition of charge and discharge voltage of 2.8~4.35V, the button battery is charged and discharged at 0.5C / 1C for 50 cycles. The final capacity retention rate after 50 weeks is the cycle performance. The final capacity retention rate after 50 weeks is the discharge capacity of the 50th week divided by the discharge capacity of the first week to obtain the cycle retention rate.
[0189] Rate test method: At 25°C, under the condition of charge and discharge voltage of 2.8~4.35V, the button battery is first charged and discharged at 0.1C for 2 weeks with a cut-off current of 0.005C, then charged and discharged at 0.33C for one week with a cut-off current of 0.05C, then charged and discharged at 0.5C for one week, charged and discharged at 0.5C for one week, charged and discharged at 1C for one week, and charged and discharged at 0.5C for one week with a cut-off current of 0.05C; the capacity discharged at 2C divided by the capacity charged and discharged at 0.1C is the rate performance at 2C.
[0190] Gas generation value test of positive electrode material:
[0191] The positive electrode materials were assembled into a 2Ah soft-pack battery, in which the positive electrode formula was positive electrode: binder: conductive agent = 96.8:1.2:2, and the negative electrode formula was negative electrode (artificial graphite): binder: conductive agent = 95.6:1.4:3; the batteries were stored in a high-temperature oven at 60°C for 7 days, and the gas production was tested by the drainage method. The obtained gas production was the 7-day gas production of the soft-pack battery per unit mass, and the unit was mL / g.
[0192] The above test results are detailed in Tables 1 and 2. (D90-D10) / D50 is expressed as "Span value".
[0193] Table 1
[0194]
[0195]
[0196] Table 2
[0197]
[0198]
[0199] Table 3
[0200]
[0201]
[0202] Table 4
[0203]
[0204] From Tables 1 to 4 above, compared with Comparative Examples 1 to 5, in Examples 1 to 20, the positive electrode material contains the element M (such as at least one of Na, K, Cs, Mg, Ca, Sr or Ba), and the concentrations X1 and X2 in the central area and the surface area of the particles satisfy 1.2≤X2 / X1≤20, and combined with the fact that the number of agglomerates in the positive electrode material accounts for less than 1%, the positive electrode material has good capacity and first effect, as well as good cycle performance and rate performance, thereby reducing the gas production of the secondary battery. After a large number of experiments, the inventor speculated that it may be because the concentration of the M element in the particles satisfies 1.2≤X2 / X1≤20, so that the content of the element M near the surface area of the particles is relatively high, and the M element increases the unit cell volume of the surface area of the particles, while the content of the element M near the center area of the particles is relatively small, so that the unit cell volume at the center area of the particles is relatively small, thereby forming a compressive stress from the surface to the center of the particles. The compressive stress can inhibit the change of the lattice volume during the charge and discharge process, inhibit the generation or diffusion of particle cracks, and thus improve the gas production performance of the positive electrode material and improve the long-term cycle performance of the positive electrode material. At the same time, combined with the range of the proportion of agglomerates in this application, an appropriate amount of agglomerate particles can shorten the transmission channel for lithium ion deintercalation during the charge and discharge process, which is beneficial to the diffusion and transmission of lithium ions, thereby helping to reduce the internal stress caused by lithium ion deintercalation during the charge and discharge process. At the same time, the strength of the agglomerate particles is relatively high, which can reduce the particle rupture phenomenon during the pole piece rolling process, and the exposed surface of the fine powder and the particles is greatly reduced, thereby improving the gas production phenomenon, thereby synergistically improving the cycle stability and rate performance of the secondary battery.
[0205] See also Figure 3 ,exist Figure 3 In (b), the content distribution of element K inside the particles in Comparative Example 2 is basically the same, while the internal distribution of the particles in Example 1 is different, such as Figure 3 (a), and the element K is more enriched near the surface. Figure 4 ,exist Figure 4 (a) shows that the agglomerates in Example 2 are less, while in Figure 4 In (b), there are more agglomerations in Comparative Example 1.
[0206] Compared with Example 1, Comparative Example 1 adopts the coprecipitation method to prepare the positive electrode material precursor, and the prepared positive electrode material does not contain element M, and the agglomerates account for a large proportion. The capacity, first efficiency and cycle performance of the positive electrode material are all reduced, and the gas production is improved.
[0207] Compared with Example 1, Comparative Example 2 adopts a co-precipitation method to prepare a positive electrode material precursor, and solid-phase doping of K and Mg elements is performed in step (3). The distribution of M element in the positive electrode material is relatively uniform, and the proportion of agglomerates is high. The capacity, first efficiency and cycle performance of the positive electrode material are all reduced, and the gas production is improved.
[0208] Compared with Example 1, no soluble M element is added in step (1) of Comparative Example 3, and the prepared positive electrode material does not contain element M. The capacity, first efficiency and cycle performance of the positive electrode material are all reduced, and the gas production is increased.
[0209] Compared with Example 1, soluble M element was added in step (1) of Comparative Example 4, and the pyrolysis temperature was adjusted to 1000 degrees. The M element was enriched in the surface area of the material, the capacity, first efficiency and cycle performance of the positive electrode material were reduced, and the gas production was increased.
[0210] Compared with Example 1, in step (3) of Comparative Example 5, a staged sintering method is adopted, and the agglomerate content in the obtained positive electrode material is higher, the capacity, first efficiency and cycle performance of the positive electrode material are reduced, and the gas production is increased.
[0211] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises an element M, wherein the element M is selected from at least one of Na, K, Cs, Mg, Ca, Sr and Ba. The positive electrode material comprises a plurality of particles, wherein the cross section of the particle comprises a central region and a surface region. The cross section of the particle is tested by an energy spectrometer, and the average concentration of the element M in the central region is measured to be X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; the particles comprise primary particles and agglomerate particles, and a SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and the total number of the primary particles and the agglomerate particles of the positive electrode material in the SEM image is N, and the number of the agglomerate particles is n, and n and N satisfy: n / N<1%, wherein the agglomerate particles are formed by agglomerating 5 or more primary particles having a particle size of less than 1 μm.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) 3.3 ≤ X2 / X1 ≤ 9.5; (2) 0.5% ≤ n / N < 1%; (3) The maximum distance between any two points on the agglomerate particles is less than 4 μm.
3. The positive electrode material according to claim 1, characterized in that The concentration of the element M is 10 ppm to 400 ppm based on the mass of the positive electrode material.
4. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the average particle size of the primary particles is 1 μm to 5 μm.
5. The positive electrode material according to claim 1, characterized in that The lattice strain ε of the positive electrode material is less than 0.1%.
6. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is: Li a Ni b Co c Q d O2, wherein 0.95≤a≤1.2, 0<b≤1, 0<c≤1, 0<d≤1, b+c+d=1, and the element Q is selected from at least one of Mn and Al.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material further contains element N, and the element N is selected from at least one of Zr, Ti, Co, Mg, W, Ce, and Y; based on the mass of the positive electrode material, the concentration of the element N is less than 5000 ppm.
8. The positive electrode material according to any one of claims 1 to 7, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The specific surface area of the positive electrode material is 0.4 m 2 / g to 0.9m 2 / g; (2) The tap density ρ1 of the positive electrode material: ρ1>2.0 g / cm 3 ; (3) The powder compaction density of the positive electrode material ρ2: ρ2 ≥ 2.8 g / cm 3 ; (4) The particle size of the positive electrode material satisfies: 1.0≤(D90-D10) / D50≤1.
5.
9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 8.
10. A secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the housing, and the electrode assembly comprises a separator and a negative electrode sheet, characterized in that: The electrode assembly further comprises the positive electrode sheet as claimed in claim 9, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.
Citation Information
Patent Citations
Lithium secondary battery
CN110048088A
Positive electrode active material, preparation method thereof, positive electrode plate and lithium ion secondary battery
CN112447951A
Secondary battery and electronic device
CN117832390A
Non-aqueous electrolyte secondary cell
CN1875505A
Positive Electrode Active Material For Lithium Secondary Battery, Method of Preparing the same, and Positive Electrode for Lithium Secondary Battery and Lithium Secondary Battery which include the positive Electrode Active Material
US20210234155A1
Cited By
Battery cell, battery device, electric device, and energy storage device
CN120300267A
Positive electrode material, positive electrode sheet and secondary battery
WO2026138736A1